2015
DOI: 10.1208/s12248-015-9743-7
|View full text |Cite
|
Sign up to set email alerts
|

Applying Biopharmaceutical Classification System (BCS) Criteria to Predict Oral Absorption of Drugs in Dogs: Challenges and Pitfalls

Abstract: Abstract. The Biopharmaceutical Classification System (BCS) has been a prognostic tool for assessing the potential effects of formulation on the human drug oral bioavailability. When used in conjunction with in vitro dissolution tests, the BCS can support the prediction of in vivo product performance and the development of mechanistic models that support formulation assessments through the generation of Bwhat if^scenarios. To date, the applicability of existing human BCS criteria has not been evaluated in dogs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(72 citation statements)
references
References 78 publications
(71 reference statements)
1
68
1
2
Order By: Relevance
“…Itraconazole is a weak base and is classified as “practically insoluble” by the United States Pharmacopeia . Because of its insolubility, ITZ is classified by the Biopharmaceutical Classification System (BCS) as Class 2, which means that oral absorption is highly dependent on the ability of the drug to dissolve in the gastrointestinal tract. For the capsule formulation, gastric acidity is required for dissolution and absorption (pKa 3.7) .…”
Section: Discussionmentioning
confidence: 99%
“…Itraconazole is a weak base and is classified as “practically insoluble” by the United States Pharmacopeia . Because of its insolubility, ITZ is classified by the Biopharmaceutical Classification System (BCS) as Class 2, which means that oral absorption is highly dependent on the ability of the drug to dissolve in the gastrointestinal tract. For the capsule formulation, gastric acidity is required for dissolution and absorption (pKa 3.7) .…”
Section: Discussionmentioning
confidence: 99%
“…Because many factors can affect drug oral absorption, marked differences in drug oral bioavailability between humans and veterinary species, and between ruminants and nonruminants, are not unusual. In this regard, the principles of the Biopharmaceutics Classification System (BCS) initially developed to assess human drug oral bioavailability have been suggested as an important prognostic tool to be extrapolated to aid oral drug evaluation and development in canine species (Papich & Martinez, ). Readers are directed to these review articles (Martinez et al ., ,b) regarding the physiological, biopharmaceutical, and formulation considerations when applying the BCS criteria to evaluate drug oral bioavailability in canine species.…”
Section: Methodsmentioning
confidence: 99%
“…The borderline for the low/high permeability must be defined when evaluating permeability (P app ) data from cell monolayer, and metoprolol is currently an acceptable and widely used marker for this purpose (Incecayir, Tsume, & Amidon, 2013;Zur et al, 2014), so metoprolol was used to be a reference standard for class in our research, and the classification results formed a good correlation with the absorption of drugs in chickens. LogP has been used for the permeability classification of canine BCS and pediatric BCS, and a LogP value greater than 1.72 as high permeability (Guimaraes et al, 2019;Papich, 2015), but the LogP only represents the lipophilic of drug molecules, and it ignores the enzymes and transporters inherent in human or animal organisms, thus, it is not surprising that predictions based only on LogP may frequently be in error, often because most drugs may be substrates for some transporter (Papich, 2015;Wu & Benet, 2010), such as some substrates (ciprofloxacin hydrochloride for P-gp and BCRP; sulfadiazine for P-gp) in our study (Zhang et al, 2018), which with a higher LogP value but a lower absorption in chicken. Moreover, we also discussed the role of pH on permeability class, and the result showed that pH has less influence on classification, except sulfamethoxazole, which was an acid drug (pKa 5.6), exhibits high class under pH 5.5 but low under pH 7.4, and it is well interpreted that acid drugs have higher permeability values at lower pH (Tolle-Sander, 2002;Yang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The United States Pharmacopeial Convention (USP) has outlined considerations for a possible veterinary BCS and the ad hoc committee suggested to develop this tool for first use in dogs (Martinez, Papich & Riviere, ). The related studies reported by Chiou, Chung, and Wu () and Papich and Martinez () showed the overall interspecies (human and dogs) correlation of F values was low (coefficient of determination, R 2 = .51 and .15, respectively). The interspecies differences including gastrointestinal physiology (GI transit rate, pH, and volume of fluid) and dosage strength were obviously observed, which indicates the extrapolation of human criteria to veterinary species is not applicable.…”
Section: Introductionmentioning
confidence: 86%